Misteri Kristus Dan Kristus Pemersatu Ciptaan Dalam Teologia Filosofis Maximus The Confessor: Sebuah Tinjauan Kritis - Minggus Minarto Pranoto (Theologia in Loco, 2018)
Amid the debate over the asymmetry of the structure of Job's dialogue with his three friends - Eliphaz, Bildad and Zophar - and the tendency of OT experts to read it linearly, leading to conclusions about the process of redaction and the redactor of the book of Job, this paper shows that Job's dialogue with three His friends are arranged in a chiastic manner with a certain composition pattern based on the number of verses. Thereby supporting the opinion of the unity of the text of the book of Job.